Development of a diagnostic PCR to detect Neoparamoeba perurans, agent of amoebic gill disease - Young, ND; Dykova, I; Barbara Nowak; Morrison, RN (2008)
The recent description of Neoparamoeba perurans as an aetiological agent of amoebic gill disease (AGD) advanced our understanding of the condition and has forced a re-evaluation of methods used for the diagnosis of AGD. Currently, there are no tools available that are both specific for N. perurans and suitable for a routine diagnostic procedure. Therefore, in this study we describe an assay to detect N. perurans. The assay, which utilizes PCR to amplify the N. perurans 18S rRNA gene, was shown to be specific and highly sensitive. Neoparamoeba perurans was detected in both gill samples and primary isolates of non-cultured gill-derived amoebae obtained during necropsy or biopsy from AGD-affected Atlantic salmon, Salmo salar L. The PCR-based assay provides a simple, flexible tool that will be a useful addition to the diagnostic repertoire for AGD. It may also be used for the genotypic screening of trophozoites during culture and could facilitate further epidemiological and ecological studies of AGD. Â© 2008 The Authors.